2004
DOI: 10.1007/s11176-005-0152-y
|View full text |Cite
|
Sign up to set email alerts
|

Influence of metal cation on chromophore properties of complexes of some d metals with α,α-dipyrrolylmethene

Abstract: In complexes of Cu 2+ , Ni 2+ , Co 2+ , Zn 2+ , and Hg 2+ with 3,3`,5,5`-tetramethyl-4,4`-dibutyl-2,2`-dipyrrolylmethene, the d-metal ion exerts an auxochromic effect on the p system of the ligand, manifested in a bathochromic shift of the first absorption band in the spectrum of the complex, compared to the free ligand. Polarization of the chromophore p system in the complexes increases in the order Zn 2+ < Hg 2+ < Co 2+ < Ni 2+ < Cu 2+ . The Hg 2+ ion in the complex with dipyrrolylmethene participates in mer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 4 publications
1
16
0
Order By: Relevance
“…Using a combination of spectroscopic and calorimetric methods Guseva et al have recently reported on the thermodynamics of dipyrromethene deprotonation and complexation as part of their work towards understanding the metal-template effect in the synthesis of porphyrins [25,[27][28][29]. The data that Guseva uses to calculate equilibrium constants for dipyrromethene complexation with Zn(II), Ni(II), Co(II), Cu(II) and Hg(II) is extracted from the absorption maxima attributed solely to ligand and homoleptic complexes in titrations and does not take into account any intermediates, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Using a combination of spectroscopic and calorimetric methods Guseva et al have recently reported on the thermodynamics of dipyrromethene deprotonation and complexation as part of their work towards understanding the metal-template effect in the synthesis of porphyrins [25,[27][28][29]. The data that Guseva uses to calculate equilibrium constants for dipyrromethene complexation with Zn(II), Ni(II), Co(II), Cu(II) and Hg(II) is extracted from the absorption maxima attributed solely to ligand and homoleptic complexes in titrations and does not take into account any intermediates, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…While the optical spectra, especially fluorescence, have been thoroughly studied for the boron complexes of dipyrromethenes, 8,9 those of simple dipyrromethenes and their metal complexes have not been extensively studied. A. I. V'yugin et al 10 examined solvent effects and showed that l max is determined by the polarization of the p system, which in turn is governed by electronic and steric factors of the metal ions. We have reported 11 that hyperconjugation of peripheral alkyl a Bending angle (y) as shown in Fig.…”
mentioning
confidence: 99%
“…Synthesis and elemental analysis, NMR 1 H-, UV-and IR-spectroscopy data for respective dipyrrine hydrobromides HL 1 ·HBr, HL 2 ·HBr and HL 3 ·HBr were described in the previous works [13][14][15].…”
Section: Methodsmentioning
confidence: 99%
“…For homoleptic zinc (II) dipyrrinates [ZnL2], which by their spectralluminescent and photo-physical properties are not inferior BODIPY [13,14], the systematic study of this effect has not yet been carried out. Important criterion for practical application of phosphors as laser dyes and other fields are their thermal stability.…”
Section: Introductionmentioning
confidence: 99%